ASSESSMENT AND FEEDBACK IN ENGLISH LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Assessment and feedback are essential components of effective English language teaching (ELT). Modern pedagogy views assessment not only as a tool for measuring knowledge but also as a means of enhancing learning through constructive and timely feedback. This article examines different types of assessment used in ELT, explores the psychological and pedagogical impact of feedback on learners, and discusses innovative strategies that promote student engagement and language development. The study emphasizes the importance of formative assessment, learner-centered feedback, and reflective practices in improving communicative competence and learner autonomy.